Reinventing Japan: From Merchant Nation to Civic Nation - Takao, Yasuo (Palgrave Macmillan, 2007)
© Yasuo Takao, 2007. All rights reserved. The book is about new dynamic forces that are driving change in Japan. It is developed around two key concepts of civil society and social capital. The focus is on pathways to Japan's social renewal that promotes stronger communities and more participatory citizenship beyond the reach of economic growth.